Penapisan Fitokimia Ekstrak Etanol Daun Kirinyuh Hasil Metode Ekstraksi Refluks dan Maserasi - Mujittaba Mumarli; Lanny Mulqie; Suwendar (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Kirinyuh (Chromolaena odorata L.) is also called weed, is a perennial shrub from the aster group with straight, brittle stems and many branches. Traditionally, kirinyuh leaves are used as a wound healing medicine, mouthwash for sore throats, cough suppressants, antimalarials, headaches, antidiarrheals, astringents, antispasmodics, antihypertensives, anti-inflammatory, diuretics, and have antiprotozoal effects. Kirinyuh leaves have an identity compound, namely the quercetin compound which is resistant to heat from flavonoid derivatives that can inhibit bacterial growth. This study aims to identify the content of compounds found in the simplex and ethanol extract of kirinyuh leaves and to determine the results of the comparison of the content of compounds found in the extracts from the reflux and maceration extraction methods. The results of phytochemical screening of simplex and ethanol extracts of kirinyuh leaves from the reflux and maceration extraction methods gave the same results indicating the presence of alkaloids, polyphenols, flavonoids, saponins, anthraquinones, tannins, and steroids.